Cutaneous Tuberculosis Occurring After a Skin Cut in a Child - (:unkn) unknown (My University, 2016)
BACKGROUND: Tuberculosis is a common problem in Turkey, and cutaneous tuberculosis is a rare form of extrapulmonary tuberculosis. Herein, the authors describe a case of cutaneous tuberculosis (lupus vulgaris) occurring after contact with a sheep. CASE: A 15-year-old boy was admitted to Marmara University School of Medicine Pendik Training and Research Hospital (Istanbul, Turkey) with delayed wound healing on the left index finger and left axillary lymphadenopathy. His medical history was unremarkable except for a wound incurred when he slaughtered a sheep 3 months before. One month after this injury, the patient developed enlargement of the left axillary lymph node on the side of the wounded extremity, and the wound turned a dark black color. The biopsy specimens obtained from the wounded skin and lymph nodes showed granulomatous reaction, but acid-fast bacilli (AFB) could not be shown with Ehrlich-Ziehl Neelsen staining. The patient tested positive in an interferon-gamma release assay. Computerized tomography scans of the thorax were normal, and early morning gastric lavage specimen was negative for AFB. The wound and axillary lymphadenopathy disappeared after institution of anti-tuberculosis therapy. CONCLUSION: Tuberculosis infection must be considered in chronic skin lesions with granulomatous reaction occurring in countries with high prevalence of tuberculosis.
Keywords: Humans; Treatment Outcome; Animals; Turkey; Adolescent; Male; Axilla; Occupational Diseases; Wound Healing; Antitubercular Agents; Isoniazid; Rifampin; Mycobacterium tuberculosis; Pyrazinamide; Sheep; Ethambutol; Finger Injuries; Abattoirs; Lupus Vulgaris; Lymphadenopathy